Venous thromboembolism in menopausal period - part one - Stachowiak, Grzegorz; Połać, Ireneusz; Stefańczyk, Ludomir; Jędrzejczyk, Sławomir; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
In this article an important topic of menopausal gynecology – venous thromboembolism (VTE) – has been analyzed. In the first part we have paid attention to VTE risk factors being characteristic for menopausal period as well as to some changes in female organism causing rise in VTE risk. One part of the article has also been spent on the influence of hormonal therapy of climacterium – both oral contraception and hormone replacement therapy – on thromboembolic complications, particularly in women with thrombophilia.